ANALISIS KELAYAKAN DAN STRUKTUR PASAR RUMPUT LAUT DI DESA SANDI KECAMATAN KALEDUPA SELATAN KABUPATEN WAKATOBI - Waode Alzarliani (Media Agribisnis, 2017)
Abstract The problems in this study are (1) how much income earned by farmers from seaweed cultivation activities in Sandi Village, South Kaledupa District (2) How much is the feasibility value of seaweed cultivation by farmers (3) How is the structure of the seaweed market in the Village South Kaledupa District. This research was carried out with the aim to determine (1) the income received by seaweed farmers (2) to determine the feasibility value of seaweed farming (3) to determine the seaweed market structure in Sandi Village, South Kaledupa District. The population in this study were all farmers who cultivated seaweed which amounted to 50 people. Determination of respondents is done by census method by taking all farmers totaling 50 respondents. The results showed that the average income obtained by farmers within 6 months amounted to IDR. 5,576,000 with an average rope length of 1277 meters used by farmers, with an income of IDR 929,333 per capita per month. That seaweed business is feasible to be cultivated and developed. The market structure faced by each marketing agency for seaweed in Sandi village is the same. Farmers and village collectors face an oligopsony market structure. Dry seaweed produced by respondents after being sold to exporters, the seaweed sold back to the Industry in Surabaya to be managed and processed further so that the market structure faced by large traders (exporters) lead to the oligopoly market. Keywords: income, feasibility, market structure, seaweed